PENGARUH DISIPLIN KERJA DAN MOTIVASI TERHADAP KINERJA PEGAWAI PADA KANTOR KECAMATAN LIMO KOTA DEPOK - Jirky Pratama; Achmad Nur Sholeh (Al Hasanah Barokah Foundation, 2025)
The objective of this research is to know partially and simultaneously the effect of work discipline and motivation on employee performance in the Limo district office, Depok. This research method is an associative study using a quantitative approach. The subjects of this study were all 53 employees of the Limo Depok District Office. While the sample used were 53 respondents using saturated sample technique. Data collection using, questionnaires, documentation, and literature study. Meanwhile, the data analysis used validity test, reliability test, normality test, multicorrelation test, heteroscedasticity test, linear regression, determination coefficient, and significant test (t test and F test). Based on the results of the study, the t count for the Work Discipline (X1) variable on performance (Y) is 1.859 <2.009. It can be concluded that the Work Discipline variable has no significant effect on performance. The t count value for the Motivation Variable (X2) on Performance (Y) is 3,867> 2,009.It can be concluded that the Motivation variable has a positive influence on performance. Obtained multiple linear regression equation model Y = 11,494 + 0,212 X1 + 0,553 X2. The R value is 0.533 or 53.3%, which means the correlation of Work Discipline and Motivation on Employee Performance in the Strong Enough category (0.400 – 0.599) with the coefficient of determination adjusted R2 (adjusted R Square) of 0.284. This shows that 28.4% of Work Discipline and Employee Motivation simultaneously (jointly) affect employee performance, while the remaining 71.6% is influenced by other factors not examined in this study.